Bromine‐Substituted Fluorene: Molecular Structure, Br–Br Interactions, Room‐Temperature Phosphorescence, and Tricolor Triboluminescence. Issue 51 (16th November 2018) - Wang, Jiaqiang; Wang, Can; Gong, Yanbin; Liao, Qiuyan; Han, Mengmeng; Jiang, Tianjiao; Dang, Qianxi; Li, Yaqin; Li, Qianqian; Li, Zhen
Abstract: Organic tribophosphorescence materials are rarely reported and the introduction of Br atoms may be a practical way to design such materials. Here four bromine‐substituted fluorene‐based derivatives are presented and BrFlu−CBr, having fluorescence‐phosphorescence dual‐emission induced not only by UV light but also by mechanical stimulus, manifests the highest phosphorescence efficiency of 4.56 % upon photoirradiation. During the grinding process, three different triboluminescent spectra were identified. Upon introduction of a mechanical stimulus, the triboluminescence emission is cyan, whereas after an extended period it changed to blue. After removing the mechanical stimulus, green‐white phosphorescent emission was observed. Careful research on single‐crystal structures and theoretical calculations demonstrate that strong Br⋅⋅⋅Br interactions are vital to facilitate spin‐orbit coupling and promote intersystem crossing, thus generating the unique properties. Abstract : Color tuning : Crystals of the fluorene derivative BrFlu−CBr exhibit fluorescence‐phosphorescence dual‐emission upon introduction of a mechanical stimulus, without excitation by a UV lamp. Upon extended exposure to the mechanical stimulus, the triboluminescence emission changes from cyan to blue. After removal of the mechanical stimulus, green‐white phosphorescence is observed.